2017
DOI: 10.3390/ijms18061250
|View full text |Cite
|
Sign up to set email alerts
|

Eplerenone-Resistant Salt-Sensitive Hypertension in Nedd4-2 C2 KO Mice

Abstract: The epithelial sodium channel (ENaC) plays critical roles in maintaining fluid and electrolyte homeostasis and is located in the aldosterone-sensitive distal nephron (ASDN). We previously found that Nedd4-2 C2 knockout (KO) mice showed salt-sensitive hypertension with paradoxically enhanced ENaC gene expression in ASDN under high oral salt intake. Eplerenone (EPL), a selective aldosterone blocker, is a promising therapeutic option for resistant or/and salt-sensitive hypertension. We examined the effect of EPL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…64 Loss of Need4-2 in mice causes salt-sensitive hypertension and enhanced renal ENaC expression 65 resistant to eplerenone. 66 We observed that spironolactone markedly increased the ratio of total over phosphorylated form of Nedd4-2 in the kidney, indicative of higher protein activity and greater ENaC internalization in AngII-infused females, but not in males. This suggests lower ENaC activity due to higher protein degradation in spironolactone-treated females.…”
Section: Discussionmentioning
confidence: 64%
“…64 Loss of Need4-2 in mice causes salt-sensitive hypertension and enhanced renal ENaC expression 65 resistant to eplerenone. 66 We observed that spironolactone markedly increased the ratio of total over phosphorylated form of Nedd4-2 in the kidney, indicative of higher protein activity and greater ENaC internalization in AngII-infused females, but not in males. This suggests lower ENaC activity due to higher protein degradation in spironolactone-treated females.…”
Section: Discussionmentioning
confidence: 64%
“…Body weight was measured twice a week. There is no literature showing the usage of sub dermic pellets of eplerenone in rodents, the choice of our dosage was similar than those chosen on previous studies where the eplerenone was added to chow (200 mg/kg pellet) (17,35,36). In our opinion the advantage of using pellets is that they deliver a constant and known dose of the drug Eplerenone to all animals regardless of the amount of food that each animal consumes.…”
Section: Animal Maintenance and Experimental Designmentioning
confidence: 99%
“…Additionally, to determine detailed characteristics of salt-sensitive hypertension of the mice, we tried a mineral corticoid receptor antagonist treatment for Nedd4-2 C2 KO mice. Finally, us and other authors [63,64], have previously found that Nedd4-2 C2 KO mice showed eplerenone-resistant salt-sensitive hypertension [65] and enhanced electrophysiological abnormalities, after myocardial infarction [66], suggesting a pivotal role of the Nedd4-2 isoform with C2 domain for cardio-renal association, with regards to target-organ damages of the subjects with salt-sensitive hypertension.…”
Section: Generation Of Nedd4-2 C2 Ko Mice and Discovery Of Salt-sensitive Hypertension With Potential Contributions To Cardio-renal Involmentioning
confidence: 71%
“…Ultimately, we found that the lack of single isoform of the gene caused a significant change in vivo, resulting in a higher oral salt intake suppressing sodium excretion in urine and elevated blood pressures, the pathophysiology of which is called "salt-sensitive" [62]. In accordance with human genetic studies, the impairment of tubular sodium transport might be pivotal in the onset and development of salt-sensitive hypertension [65,66].…”
Section: Discussionmentioning
confidence: 84%